Macroeconomic uncertainty and the impact of oil shocks - Ine Van Robays (European Central Bank (ECB), 2012)
This paper evaluates whether macroeconomic uncertainty changes the impact of oil shocks on the oil price. Using a structural threshold VAR model, we endogenously identify different regimes of uncertainty in which we estimate the effects of oil demand and supply shocks. The results show that higher macroeconomic uncertainty, as measured by higher world industrial production volatility, significantly increases the responsiveness of oil prices to oil shocks. This implies a lower price elasticity of oil demand and supply in the uncertain regime, or in other words, that both oil curves become steeper when uncertainty is high. The difference in oil demand elasticities is both statistically and economically meaningful. Accordingly, varying uncertainty about the macroeconomy can explain time variation in the oil price elasticity and hence in oil price volatility. Also the impact of oil shocks on economic activity appears to be significantly stronger in uncertain times.
Keywords: E31; E32; Q41; Q43; 330; Oil prices; price elasticity; sign restrictions; threshold VAR; uncertainty